Basic Remarks on Acidity. Issue 16 (15th March 2018) - Himmel, Daniel; Radtke, Valentin; Butschke, Burkhard; Krossing, Ingo
Abstract: This Review provides a unified view on Brønsted acidity. For this purpose, a brief overview of the concepts acidity, acid strengths, and pH value is given, including problems, proposed solutions, and the use of the pHabs / p H a b s H 2 O scale as a unifying concept. Thereafter, some examples of the accessibility and application of unified pHabs values are given. The Review is rounded off with the analogy of acid‐base chemistry to redox chemistry with the introduction of the unified redox scale peabs . The combination of pHabs and peabs values in the protoelectric potential map (PPM), as elaborated in ongoing studies on the thermochemistry of single ions, provides a means to classify and to compare all possible acid‐base/redox reactions in a medium‐independent and, thus, unified fashion. Abstract : Unified acidity: One scale for all ! How can Brønsted acidity be compared in different solvents? How can the acid strengths of liquid and gaseous acids be compared? How can their properties be accurately extracted thermodynamically for applications such as liquid chromatography, polymerization, catalysis, and other areas? Unified acidity based on the chemical potential of the proton allows for all of this and much more.